Confusion in the United States’ Afghan Policy and Pakistan’s Neo-Realist Responses - Dr. Fida Bazai .; Sohail Anwer; Samreen Bari Aamir; Prof. Dr. Sayeda Daud; Amjad Rashid (Al-Qanṭara, 2023)
With the emergence of the Taliban as successful insurgent movement, which eventually defeated the United States and International forces in Afghanistan, it is necessary to analyze the bilateral relationship between Islamabad and Washington on the issue of the Afghan Taliban from major International Relations theoretical perspectives in order to reach a conclusion on the responses of the Pakistani government on the issue of the Afghan Taliban. The Afghan Taliban as a group has always been the top priority of the United States in the war in Afghanistan. The confusion over the principle question of the status of the Afghan Taliban had been a major cause of the United States’ policy failures in Afghanistan. If the United States had been clear over the question of the Afghan Taliban, they would have reached a different conclusion, which would have been different result than the current one. One of the major mistakes in the United States’ policy towards Afghanistan was framing of the Taliban as different from Al-Qaeda. It is correct that Al-Qaeda and the Afghan Taliban were separate entities, but they both were against the United States’ objectives in Afghanistan. The objectives of the US policy should not have been the same in 2018 and 2019 as at the time of 9/11. They had evolved over the period of two decades war in Afghanistan. The strategic retreat of the United States from Kabul after two decades of war and investment of trillion of dollars was the result of confusion over the status of the Afghan Taliban. The policy makers in Washington had always been separating the Afghan Taliban from Al-Qaeda. It is true that the Afghan Taliban was not as dangerous as Al-Qaeda in term of attacking the United States at home, but they were at war with the US in Afghanistan. The strategic question in the policy discussion should have been how to win the war in Afghanistan irrespective of its strategic significance for the United States’ security. A policy around this premise would have resulted in different situation. It would have shifted the debate towards winning the war rather than discussing the importance of Afghanistan for the United States’ security. This was one factor that had determined Pakistan’s cooperation with the US on Afghan Taliban.